الربيع في شعر إقبال وشوقي دراسة مقارنة: Spring in the Poetry of Iqbal and Shawqi: A Comparative Study - هند عبد الحليم محفوظ رمضان (الدراسات الإسلامية, 2020)
This article aims to study the usage of spring in poetry of two renowned Muslim poets i.e., Muhammad Iqbal (d. 1938) and Ahmad Shawqi (d. 1932) comparatively. Despite their separate homelands and geographical distances, they belonged to one generation and continued to produce poetry until the third decade of the twentieth century. They were educated in the West. Iqbal studied in London and Germany and Shawqi studied in France. Both of them enjoy a prominent place in their homelands. Iqbal is undisputedly the poet of the Orient (shair-i mashriq) while Shawqi is unanimously the prince of the (Arab) poets (amir al-shuara). Iqbal calls for a different poetic horizon, mixing spectra of the elements of nature and its beautiful scenery, combining the beauty of language and delicacy of vocabulary, and producing accurate expressions in the colourful form of the subcontinental environment. His poems full of warm sincerity will remain immortal, and so will his hymns venerating nature, purity, and beauty. Shawqi, on his part, responded in many of his poems to the elements of nature. His poems are the fruit of hot temper and explosive mood where reason does not interfere to spoil the poetic image. For this reason, his poems do not lose the childhood spirit that one finds in his homage to the images of nature and its charm, like the Nile that embraced the ancient Egyptian civilization, nocturnal life, the crescent and vernal flowers.